The Influence of HCl Concentration on the Rate of the Hydrolysis–Condensation Reaction of Phenyltrichlorosilane and the Yield of (Tetrahydroxy)(Tetraphenyl)Cyclotetrasiloxanes, Synthesis of All Its Geometrical Isomers and Thermal Self-Condensation of Them under “Pseudo”-Equilibrium Conditions - Irina M. Petrova; Yury I. Lyakhovetsky; Nikolai S. Ikonnikov; Nataliya N. Makarova (Molecules, 2021)
The rate of hydrolysis–condensation reaction of phenyltrichlorosilane in water-acetone solutions and the product yields were shown to significantly depend on the concentration of HCl (CHCl) in the solutions. The main product of the reaction was all-cis-(tetrahydroxy)(tetraphenyl)cyclotetrasiloxane. This was different from the earlier published results of analogous reactions of m-tolylSiCl3, m-ClPhSiCl3, and α-naphtylSiCl, in which some products of other types were formed. For example, trans-1,1,3,3-tetrahydroxy-1,3-di-α-naphtyldisiloxane was obtained in the case of α-naphtylSiCl3. All-cis-(tetrahydroxy)(tetraphenyl)cyclotetrasiloxane was treated in acetone with HCl to give the other three geometric isomers (cis-cis-trans-, cis-trans-, and all-trans-). The thermal self-condensation of these four isomers under “pseudo”-equilibrium conditions (under atmospheric pressure) was investigated in different solvents, in quartz or molybdenum glass flasks. The compositions of the products were monitored by APCI-MS and 29Si NMR spectroscopy. It was shown that all-cis- and cis-cis-trans-isomers in toluene or anisole mostly gave the cage-like Ph-T8,10,12,14 and uncompleted cage-like Ph-T10,12OSi(HO)Ph compounds. In contrast to these two isomers, the cis-trans–isomer in toluene mainly formed dimers with the loss of one or two molecules of water. However, in acetonitrile, significant amounts of Ph-T10,12 and Ph-T10,12OSi(HO)Ph species were formed along with the dimers. All-trans-isomer did not enter into the reaction at all.